Studi Terhadap Perilaku Sosial Emosional “VN” Anak Usia 4 Tahun Kelas A di TK Xaverius 7 Palembang - Septiana, Anis; Darmawani, Evia; Jaya, Melinda Puspita Sari (Institut Teknologi Pendidikan Indonesia, 2023)
Early childhood VN often shows symptoms of social-emotional behavior that are different from their peers; does not respond to teacher calls and learning activities, often cries accompanied by tantrums and self-harm. The main subjects in this study were 4-year-old children at Xaverius 7 Palembang Kindergarten and the supporting subjects were parents and teachers. The research method used is descriptive qualitative method with case studies. The data used are primary and secondary data. Primary data through direct observation of VN in class and secondary data from interviews with teachers and parents. Observation data collection techniques, documentation and interviews. Data analysis techniques in research are guided by Miller and Hebarmam. The results of the study showthe causes regarding VN's social-emotional behavior; 1). Parents' attention is divided with their younger siblings and language development is disrupted due to limited time for parents to train children to repeat the initial language, VN tends not to be ready to share love with their siblings in attempts to refuse or ask for attention by hurting themselves. Very minimal opportunities to integrate with peers in the neighborhood. 2). Efforts that have been made by the school; communicate with parents (parenting), provide time for problem solving in VN, provide special time to communicateand involve VN in all activities at school. In conclusion VN tends to experience psycho-socialemotional disorders, limited understanding and family time to give attention. Suggestions still have an opportunity with awareness from the family to work with teachers to provide time to give special attention.